How do Organizational Learning and Market Conditions Affect the Relationship between Entrepreneurial Orientation and Firm Growth? A Preliminary Analysis on Small and Medium Size Hotels in Peninsular Malaysia - Kasim, Azilah; Altinay, Levent (International Journal of Economics and Financial Issues, 2016)
This is a preliminary analysis on the influence of organizational learning and market conditions on the relationships between entrepreneurial orientation and growth of small and medium size hotels in Peninsular Malaysia. Responses from 254 hotel managers/owners were analyzed using regression analysis to test the hypotheses. The findings indicate that organisational learning fully mediates the relationship between entrepreneurial orientation and SME growth. They also showed the moderating effect of market conditions in the relationship. Implications of the findings are discussed at the end of the paper. Keywords: organizational learning, market conditions, entrepreneurial orientation, firm growth, small and medium size hotels JEL Classifications: M10, M14